2021
DOI: 10.1155/2021/5587441
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular Characteristics and New Prognostic Targets for Thymoma by Multiomics Analysis

Abstract: Background. Thymoma is a heterogeneous tumor originated from thymic epithelial cells. The molecular mechanism of thymoma remains unclear. Methods. The expression profile, methylation, and mutation data of thymoma were obtained from TCGA database. The coexpression network was constructed using the variance of gene expression through WGCNA. Enrichment analysis using clusterProfiler R package and overall survival (OS) analysis by Kaplan-Meier method were carried out for the intersection of differential expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…TCGA’s studies of thymoma have shown recurrent mutations in the GTF2I gene and suggested this gene as a potential drug target for this disease. 23 , 24 , 25 Our findings confirm the prevalence of the SNVs/InDels variants in GTF2I in thymoma. Results have been reported in several articles which have been presented in the Forest and Funnel plots.…”
Section: Discussionsupporting
confidence: 79%
“…TCGA’s studies of thymoma have shown recurrent mutations in the GTF2I gene and suggested this gene as a potential drug target for this disease. 23 , 24 , 25 Our findings confirm the prevalence of the SNVs/InDels variants in GTF2I in thymoma. Results have been reported in several articles which have been presented in the Forest and Funnel plots.…”
Section: Discussionsupporting
confidence: 79%
“…Many studies have analyzed mRNA expression profiles in TETs [ 4 , 13 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. However, the results are difficult to compare due to differences in the study focus, methodology, number of samples, controls (e.g., TH vs. normal thymus, TH vs. TC, TH with and without myasthenia gravis).…”
Section: Altered Gene Expression and Non-coding Rna Network In Thymomasmentioning
confidence: 99%
“…THs with GTF2I mutations (type A and AB thymomas) were enriched for genes related to human embryonic stem cell pluripotency and Wnt/β-catenin signaling [ 82 ], lymphocyte-rich type B1 and B2 thymomas were enriched for genes related to T-cell receptor signaling, CTLA4 signaling, and ICOS/ICOSL signaling, whereas type B3 thymomas overexpressed genes related to G protein-coupled receptor signaling, Toll-like receptor signaling regulation of epithelial–mesenchymal transition (EMT) as well as NF-κB, EGF, FAK, and telomerase signaling. Differentially regulated pathways that were identified in more than one study included cell cycle regulation [ 4 , 72 , 79 , 81 ], MAPK/ERK signaling [ 4 , 78 ], hormone signaling [ 4 , 72 ], Wnt signaling [ 78 , 82 ], and apoptosis [ 4 , 81 ]. In a study by Badve et al, the top pathways associated with metastasis were amino acid metabolism, steroid and glycosphingolipid biosynthesis, cell cycle checkpoint proteins, and Notch signaling [ 72 ].…”
Section: Altered Gene Expression and Non-coding Rna Network In Thymomasmentioning
confidence: 99%
“…In the past decade, many investigations have been conducted in an effort to characterize the molecular profile of thymic epithelial neoplasms, including thymoma. Thymomas typically have low mutational burdens and a variety of copy number abnormalities [ 44 , 45 ] (summarized in Table 2 ). The observed low mutation burden in thymomas has been associated with the smaller number of somatic mutations present in the DNA of neoplastic cells [ 46 ].…”
Section: Immunohistochemical and Molecular Characteristicsmentioning
confidence: 99%
“…The most common molecular alteration in thymoma type A, type AB, type B2, and type B3 is the loss of heterozygosity across chromosome 6 (the 6q25.2-p25.3 region contains the FOXC1 tumor suppressor gene) [ 45 , 47 ]. This particular alteration was not detected in thymoma type B1.…”
Section: Immunohistochemical and Molecular Characteristicsmentioning
confidence: 99%